Relationship between pulmonary hypertension and peripheral vascular calcification in dialysis patients - LEI Xiao-mei; LI Zhi-cheng (Linchuang shenzangbing zazhi)
Objective To discuss the relationship between pulmonary hypertension and peripheral vascular calcification in dialysis patients,and provide the basis for the prevention and treatment of pulmonary hypertension.Methods In this retrospective study,we included 172 ESRD patients undergoing dialysis(n= 88 for hemodialysis,and n = 84 for peritoneal dialysis) in West China Hospital of Sichuan University.Inclusion criteria included dialysis age >3 months,stable condition,and regular dialysis.The exclusion criteria included pregnancy,HIV infection,serious infection,liver disease,active wasting diseases(such as malignant tumor or tuberculosis).The patients with acute myocardial infarction,heart failure,acute cerebrovascular disease,primary parathyroid disease,parathyroid gland resection,surgery,trauma and severe malnutrition were also excluded.All patients had the echocardiography.Pulmonary hypertension was defined when pulmonary artery systolic pressure was greater than 37 mmHg in all patients subject to echocardiography.Using both hands and pelvic X-ray,vascular calcification was observed.Results The incidence of pulmonary hypertension in HD patients was significantly higher than in PD patients(51.2%vs.22.7.5%).The dialysis patients with pulmonary hypertension had more severe vascular calcification than patients without pulmonary hypertension.Multifactor analysis revealed that severe vascular calcification(OR= 2.68),mitral valve disease(OR=7.79),HD(OR = 3.35),and larger left atrial diameter(OR= 11.39) were independent risk factors for pulmonary hypertensioa Conclusions The incidence of pulmonary hypertension in hemodialysis patients was higher than in peritoneal dialysis patients.Vascular calcification could be independent risk factors for pulmonary hypertension in dialysis patients,so preventing the occurrence of vascular calcification in the dialysis patients may have important clinical significance for pulmonary hypertension